Effect of silver (Ag) and antimony (Sb) substitution on Ba-site of porous structured YBA2CU306 superconductor / Fariesha Farha Ramli - Ramli, Fariesha Farha (2011)
In this work, the effect of silver (A( , ) and antimony (Sb) substitution on Ba-site of porous structure YBa2Ci130 (Y BCO) superconductor was investigated. Polycrystalline sucrose as used as a supplementary filler to create the open pores in the structure. Two series of sample with a nominal composition of YBa2 AgCu3Oo and YBa2.SbCu3O6 where x = 0.05. 0.10, 0.15, 0.20, 0.30. 0.40 and 0.50 were synthesized and characterized. Standard sample and porous YBa2Cu306 were also prepared for comparison. All the samples were prepared via solid state technique and undergo characterization by using X-ray diffraction (XRD) method, resistivity measurement technique and Scanning Electron Microscopic (SEM) equipment. All porous Ag doped sample showed metallic behavior at the normal state and have TC onset around 90 K. T zero was decreased as the Ag concentration increased. Optimum Ag concentration was achieved at x = 0.20 where TC zero and Jc at 70 K has the highest value of 87 K and 16.50 A/cm respectively.